William Orr papers - Orr, William, 1860-1939.; Orr, Charlotte Pettis
Correspondence, diaries, speeches, reports, articles, printed matter, memorabilia, and other papers relating chiefly to Orr's service as education adviser for the YMCA in Europe, primarily Eastern Europe. Also includes material pertaining to Orr's earlier travels in Europe; a draft of his unpublished work, "Seven Years under Twenty-Seven Flags"; notes on a geological survey of Springfield, Mass.; and articles and other papers of Orr's first wife, Charlotte Pettis Orr.
Educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Young Men's Christian associations -- Europe; Education -- Eastern, Europe; Education -- Europe; Geology -- Massachusetts -- Springfield; Europe -- Description and travel; Educators